Defective DNA base excision repair in brain from individuals with Alzheimer's disease and amnestic mild cognitive impairment - Weissman, Lior; Jo, Dong-Gyu; Sørensen, Martin M; de Souza-Pinto, Nadja C; Markesbery, William R; Mattson, Mark P; Bohr, Vilhelm A (Nucleic acids research, 2007)
Oxidative stress is thought to play a role in the pathogenesis of Alzheimer's disease (AD) and increased oxidative DNA damage has been observed in brain tissue from AD patients. Base excision repair (BER) is the primary DNA repair pathway for small base modifications such as alkylation, deamination and oxidation. In this study, we have investigated alterations in the BER capacity in brains of AD patients. We employed a set of functional assays to measure BER activities in brain tissue from short post-mortem interval autopsies of 10 sporadic AD patients and 10 age-matched controls. BER activities were also measured in brain samples from 9 amnestic mild cognitive impairment (MCI) subjects. We found significant BER deficiencies in brains of AD patients due to limited DNA base damage processing by DNA glycosylases and reduced DNA synthesis capacity by DNA polymerase β. The BER impairment was not restricted to damaged brain regions and was also detected in the brains of amnestic MCI patients, where it correlated with the abundance of neurofibrillary tangles. These findings suggest that BER dysfunction is a general feature of AD brains which could occur at the earliest stages of the disease. The results support the hypothesis that defective BER may play an important role in the progression of AD.